Complications From Left Atrial Appendage Exclusion Devices - Perrotta, Laura (J Atr Fibrillation, 2014)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and has been identified as an independent risk factor for stroke. Prevention of thromboembolic events has been based on oral anticoagulation (OAC) using Vitamin K antagonists (VKA). However, long-term OAC medication is limited by an increased bleeding risk and a low patient compliance. Relying on the observation that the majority of cardiac thrombi originate from the left atrial appendage (LAA) different devices aiming for LAA closure have been proposed. This review will discuss contemporary LAA closure devices with special emphasis on procedure related complications.